2015
DOI: 10.1016/j.ancr.2015.08.001
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: Electrochemical behavior of kaempferol and its determination in presence of quercetin employing multi-walled carbon nanotube modified carbon paste electrode

Abstract: Electrochemical behavior of kaempferol and its determination in presence of quercetin employing multiwalled carbon nanotube modified carbon paste electrode, Analytical Chemistry Research (2015), Abstract Electrocatalytic oxidation of kaempferol in presence of quercetin using multiwalled carbon nanotubes modified carbon paste electrode (MWCNTs/CPE) in phosphate buffer of pH 7.73. AbstractThe electrochemical behavior of kaempferol was investigated by cyclic voltammetry (CV) and square wave voltammetry (SWV) at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Teng et al (2019) isolated carpaine from alkaloidal hexane extract of Papaya leaves and confirmed the identity of the compound "carpaine" by NMR, MS, FT-IR, and X-ray crystal data (Teng et al, 2019) Akhila and Vijayalakshmi (2015) have reported and identified 21 compounds present in the aqueous extracts of the leaves. They were tocopherol, ascorbic acid, carpaine, deoxykaempferol, kaempferol, deoxyquercetin, quercetin, dicoumarol, coumaroylquinic acid, coumarin, folic acid, cysteine, homocysteine, cysteine sulphoxide, l glutamic acid, p-coumaroyl alcohol, dimethoxy phenol, umbelliferone, phenylalanine, caffeoyl alcohol, and methyl nonyl ketone (Akhila and Vijayalakshmi, 2015;Dar et al, 2016;Karakaya et al, 2019). Another study revealed the presence of decylene, transgeranylacetone, methyl tridecanoate, palmitic acid, myristic acid, hexadecanoic acid, linolelaidic acid, methyl cis-6-octadecenoate, stearic acid, oleic acid, 15-tetracosenoic acid, methyl heptacosanoate, trans-13-docosenoic acid, methyl erucate, methyl behenate, heneicosanoic acid, farnesyl cyanide in n-hexane, and methanol (60:40% ratios) extract of the leaves.…”
Section: Chemical Composition Of Carica Papaya L Leavesmentioning
confidence: 99%
“…Teng et al (2019) isolated carpaine from alkaloidal hexane extract of Papaya leaves and confirmed the identity of the compound "carpaine" by NMR, MS, FT-IR, and X-ray crystal data (Teng et al, 2019) Akhila and Vijayalakshmi (2015) have reported and identified 21 compounds present in the aqueous extracts of the leaves. They were tocopherol, ascorbic acid, carpaine, deoxykaempferol, kaempferol, deoxyquercetin, quercetin, dicoumarol, coumaroylquinic acid, coumarin, folic acid, cysteine, homocysteine, cysteine sulphoxide, l glutamic acid, p-coumaroyl alcohol, dimethoxy phenol, umbelliferone, phenylalanine, caffeoyl alcohol, and methyl nonyl ketone (Akhila and Vijayalakshmi, 2015;Dar et al, 2016;Karakaya et al, 2019). Another study revealed the presence of decylene, transgeranylacetone, methyl tridecanoate, palmitic acid, myristic acid, hexadecanoic acid, linolelaidic acid, methyl cis-6-octadecenoate, stearic acid, oleic acid, 15-tetracosenoic acid, methyl heptacosanoate, trans-13-docosenoic acid, methyl erucate, methyl behenate, heneicosanoic acid, farnesyl cyanide in n-hexane, and methanol (60:40% ratios) extract of the leaves.…”
Section: Chemical Composition Of Carica Papaya L Leavesmentioning
confidence: 99%